2006
DOI: 10.1245/s10434-006-9081-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Loss of Heterozygosity for Tumor-Suppressor Genes Can Accurately Classify and Predict the Clinical Behavior of Mucinous Tumors Arising From the Appendix

Abstract: Mutational profiling of accumulated allelic loss and point mutational damage correlated strongly with histopathologic definitions of pseudomyxoma peritonei disease and helped to predict the prognosis of these patients. FMR, along with histopathology, offers a comprehensive classification of these rare tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
3
19
0
Order By: Relevance
“…26 Our current, prospectively collected molecular data confirm the results from the previous study: highgrade mucinous adenocarcinomas (grades G2 and G3) more frequently accumulate allelic loss and mutational damage compared with low-grade (Grade G1) tumors. We found that the presence of high frequency LOH (fractional mutation rate Z25%) is also associated with poor survival.…”
Section: Molecular Comparison Of Disseminated Appendiceal Mucinous Nesupporting
confidence: 88%
See 4 more Smart Citations
“…26 Our current, prospectively collected molecular data confirm the results from the previous study: highgrade mucinous adenocarcinomas (grades G2 and G3) more frequently accumulate allelic loss and mutational damage compared with low-grade (Grade G1) tumors. We found that the presence of high frequency LOH (fractional mutation rate Z25%) is also associated with poor survival.…”
Section: Molecular Comparison Of Disseminated Appendiceal Mucinous Nesupporting
confidence: 88%
“…Each sample was analyzed by 16 PCR reactions for individual polymorphic microsatellites situated at nine genomic regions (1p, 3p, 5q, 7q, 9p, 9q, 10q, 17p, and 18q) in proximity to tumor suppressor genes which have previously found to be mutated in patients with disseminated appendiceal mucinous neoplasms, as previously described. 26 The Genbank accession information for the microsatellite markers and cytogenetic localization are as follows: D1S407: 1p36.21; D1S171: 1p36; D3S1539: 3p26; D3S516: 3p26; D5S1384: 5q23; D5S615: 5q23; D7S486: 7q31; D7S1530: 7q31; D9S251: 9p21; D9S1748: 9p21; D9S252: 9q24; D10S520: 10q23; D10S1173: 10q23; D17S974: 17p13; D17S1289: 17p13; D18S487: 18q21. The PCR products were analyzed by capillary electrophoresis on an ABI 3130 (Applied Biosystems).…”
Section: Molecular Analysismentioning
confidence: 99%
See 3 more Smart Citations